2013
DOI: 10.1111/jzo.12010
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence between the southern river otter and the alien invasive North American mink in marine habitats of southern Chile

Abstract: The interaction between native and introduced predators can be an important determinant of the success of introduced species and of the magnitude of their effects. In Europe, it has been shown that the American mink Neovison vison can be affected by native competitors; however, such evidence has not been found in South America. We studied the southern river otter Lontra provocax and the American mink at five marine sites, where they coexisted, and at one freshwater site, where only mink were present, in southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
1
11
0
1
Order By: Relevance
“…The average annual temperature is below 10°C (Veblen and Schlegel 1982; Toledo and Zapater 1989). River geomorphology was classified according to Montogomery and Buffington (1998) and seashore geomorphology according to Medina-Vogel et al (2013).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The average annual temperature is below 10°C (Veblen and Schlegel 1982; Toledo and Zapater 1989). River geomorphology was classified according to Montogomery and Buffington (1998) and seashore geomorphology according to Medina-Vogel et al (2013).…”
Section: Study Areamentioning
confidence: 99%
“…Depending on the study site, due to logistical constrains, it took between 3 and 9 days to deploy all traps, and each trapping campaign was between 4 to 23 days long and ended after 4 consecutive days without any mink trapped and no field signs found, or when some traps were stolen. Previous studies showed the strong preference of minks on marking under dense vegetation, steep river banks, behind rocks and under roots, in narrow passages, and in major intensity in shallow seashores (Medina 1997;Medina-Vogel et al 2013). Hence, cage traps were set close or inside these features and normally a couple of meters away from the water.…”
Section: Trappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Minks likely become infected after preying on rodents. In fact, studies carried out in the same region as our study demonstrate that mink preys heavily on rodents (Medina-Vogel et al 2013), and that rodents may become infected by contact with garbage and contaminated water (Smith and Rochowski 2011). In the south of Chile, rodents present high rates of Leptospira infection (Zunino and Pizarro 2007).…”
Section: Resultsmentioning
confidence: 89%
“…El visón americano colonizó distintas áreas del sur de Chile tras la instalación de granjas peleteras desde donde se escaparon o fueron liberados cuando su explotación económica dejó de ser rentable (Iriarte 2008). Actualmente se desconoce el efecto de este carnívoro en los depredadores nativos de Huinay, así como en sus presas principales, por lo que sería interesante su estudio, como se ha hecho en otras zonas del sur de Chile (Medina-Vogel et al 2013). Existe un considerable debate sobre la utilidad de las encuestas como alternativa a los tradicionales estudios ecológicos de campo.…”
Section: Discussionunclassified